Antibiotic Resistance in the Philippines: Environmental Reservoirs, Spillovers, and One-Health Research Gaps - Ng, Charmaine; Abrazaldo, Josephine; de Vera, Patrick; Goh, Shin Giek; Tan, Boonfei (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) remains a major health threat in the Philippines, where high antimicrobial use, intensive aquaculture, and recurrent typhoon-driven flooding and monsoon seasons shape distinctive transmission pathways. This narrative review synthesizes published Philippine data across clinical, agriculture, and environmental sectors to map evidence and gaps relevant to policy. Clinically, vancomycin resistant Enterococcus faecium is 23%, Klebsiella pneumonia shows ∼15% carbapenem resistance, and Escherichia coli resistance to third generation cephalosporins (3GC) and fluoroquinolone are ∼43 and ∼46%, respectively. In food animals, ceftriaxone resistance in non-typhoidal Salmonella (NTS) increased from ∼8% (2010) to ∼43% (2020s), with ciprofloxacin resistance between 14 and 23%. Environmental studies report extended spectrum beta-lactamase (ESBL)-producing E. coli in Manila estuaries and multiple antibiotic resistance (MAR) indices of up to 0.15 in tributaries. Hospital sewage and nearby rivers have yielded carbapenemase-producing Enterobacterales (CPE) bearing blaNDM/blaKPC in clinically relevant lineages (e.g., E. coli CC10, K. pneumoniae ST147). Cross sector comparisons remain constrained by method heterogeneity and data gaps. To operationalize One-Health monitoring, we propose (i) a two window surveillance design: late dry baseline and 24–72 h post-storm flood pulses; and (ii) a two tier analytics model: Tier 1 HT-qPCR ARG/MGE panels at regional hubs for rapid screening, and Tier 2 metagenomics/isolate whole genome sequencing (WGS) at national hubs for source attribution and plasmid tracking. We translate these findings into a modular AMR risk assessment toolkit to prioritize surveillance and targeted interventions.